2020
DOI: 10.1097/md.0000000000021576
|View full text |Cite
|
Sign up to set email alerts
|

Improved Parkinsons disease motor score in a single-arm open-label trial of febuxostat and inosine

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 58 publications
(56 reference statements)
0
21
0
Order By: Relevance
“…Moreover, Watanabe and colleagues conducted an open-label, single-arm, multicenter trial to investigate the efficacy and safety of the co-administration of febuxostat, a xanthine oxidoreductase inhibitor, and inosine in PD patients [ 15 ]. Patients received febuxostat 20 mg and inosine 500 mg twice a day for 8 weeks, and the primary endpoint was the change in the MDS-UPDRS Part III score immediately prior to and after 57 days of treatment [ 15 ]. After treatment, serum hypoxanthine levels were significantly increased, and the MDS-UPDRS Part III score was significantly decreased [ 15 ].…”
Section: Inosine In Pdmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Watanabe and colleagues conducted an open-label, single-arm, multicenter trial to investigate the efficacy and safety of the co-administration of febuxostat, a xanthine oxidoreductase inhibitor, and inosine in PD patients [ 15 ]. Patients received febuxostat 20 mg and inosine 500 mg twice a day for 8 weeks, and the primary endpoint was the change in the MDS-UPDRS Part III score immediately prior to and after 57 days of treatment [ 15 ]. After treatment, serum hypoxanthine levels were significantly increased, and the MDS-UPDRS Part III score was significantly decreased [ 15 ].…”
Section: Inosine In Pdmentioning
confidence: 99%
“…Patients received febuxostat 20 mg and inosine 500 mg twice a day for 8 weeks, and the primary endpoint was the change in the MDS-UPDRS Part III score immediately prior to and after 57 days of treatment [ 15 ]. After treatment, serum hypoxanthine levels were significantly increased, and the MDS-UPDRS Part III score was significantly decreased [ 15 ]. Overall, these data indicate that the co-treatment of febuxostat and inosine could be safe and effective in improving symptoms in PD patients [ 15 ].…”
Section: Inosine In Pdmentioning
confidence: 99%
See 2 more Smart Citations
“…Compensation by the hub, which is hierarchically located at the upper level of the disrupted lower network, may increase the energy requirements of the same region, and contribute to energy failure and accumulation of pathological proteins ( Saxena and Caroni, 2011 ; de Haan et al, 2012 ). Treatment with febuxostat and inosine increased blood hypoxanthine and ATP in healthy adults, and a preliminary trial in 30 patients with Parkinson’s disease demonstrated symptomatic improvement ( Watanabe et al, 2020 ).…”
Section: Possible Cellular Mechanisms Of Hub Vulnerability In the Aging Brain And Neurodegenerationmentioning
confidence: 99%